Concentrations and sources of heavy metals in shallow sediments in Lake Bafa, Turkey - Algül, Fulya (Sci Rep, 2020)
The concentrations and sources of heavy metals in shallow sediments in Lake Bafa were investigated. The concentrations of nine heavy metals and the total organic carbon content in sediment samples were determined for between Summer 2015 and Spring 2016. The mean contents of heavy metals were in decreasing order Fe > Mn > Ni > Cr > Zn > Cu > Co > Pb > Cd. Sediment quality guidelines indicate that Cr, Cu, and Ni pose a considerable threat to the aquatic ecosystem in Lake Bafa. Site L3 was found to be contaminated with Cd, Cr, and Ni, and the pollution load indices suggest that these metals had anthropogenic sources. The sediment samples were notably enriched with Cd and Ni. There is no consistent trend for seasonal effect in terms of the sample locations. However, at all sampling points, an increase in heavy metal concentrations was observed in the autumn. The results of a multivariate analysis indicate that the sources of Co, Cu, Fe, Mn, Pb, and Zn were all natural, the sources of Cd were anthropogenic, and the sources of Ni and Cr were both anthropogenic and natural. These results highlight that Cd, Cr, and particularly Ni represent the most serious threat in terms of heavy metal pollution in the ecosystem of the lake.